Case report: a rare case of hereditary colorectal cancer and brain tumor with café au lait spots in a child: constitutional mismatch repair deficiency (CMMRD) syndrome - Zubair Khurshid; Mishraz Shaikh; Tarek Talaat Harb Elkadi (Egyptian Pediatric Association Gazette)
Abstract Background Colorectal carcinoma (CRC) is rarely seen in the pediatric population. Hereditary cancers due to mismatch repair deficiency cause colorectal, brain, hematological malignancies, and other tumors in early childhood. Case presentation We present an 11-year-old boy who presented with colorectal cancer and brain tumor due to constitutional mismatch repair deficiency syndrome with a family history of sibling deaths due to brain tumors. Conclusions Hereditary cancers arising due to mismatch repair gene mutations cause early colorectal and brain cancers in children. The members of such families should be genetically screened for any mutations.